CARBONATE DIAGENESIS DURING THERMO-CONVECTION: APPLICATION TO SECONDARY POROSITY GENERATION IN CLASTIC RESERVOIRS - Genthon P.; Schott J.; Dandurand J.L. (My University, 1997)
Carbonate mass transfer due to a slow convective circulation within a sedimentary layer is modeled to assess the geometry of dissolution and precipitation zones as well as the time constant necessary for a significant dissolution or precipitation of solid phases. This study is focused on the effect of aluminosilicates, and in particular kaolinite on the time constant and location of carbonate diagenetic reactions and thus on porosity redistribution. When kaolinite, albite and chlorite are present in a carbonate system, dissolution and precipitation rates are increased by a factor up to 50 compared to the pure carbonates case. Moreover, carbonates tend to dissolve with increasing temperature, and secondary porosity occurs at the bottom of downwelling currents. It should be emphasized, however, that the net carbonate dissolution may result from calcite precipitation associated with dolomite dissolution. In several instances, the whole chemical system is dominated by a single reaction, such as cation exchange in carbonates or the acid-base reaction between kaolinite and chlorite. This generally implies that the dissolution of every solid phase is proportional to that of calcite. Moreover, when the variance of the chemical system is sufficiently low, absolute dissolutions can be analytically derived from the variation with temperature of the reaction equilibrium constants. This implies that a sufficient knowledge of the chemical system behavior could avoid numerical computations. It is shown that uncertainties in the thermodynamical properties of aluminosilicates minerals may result in variations of more than one order of magnitude in computed dissolution rates. In some cases, the dominant reaction in the system is changed and therefore the whole pattern of dissolution and precipitation zones is disrupted. This points out the need of reliable thermodynamic data bases to model mass transfer induced by convective circulations in porous layers.
Keywords: DIAGENESIS; CARBONATES; CONVECTION; SEDIMENTARY BASINS; HYDROLOGY; MASS TRANSFER